INFECTION THAT UNDERLIES THE OCCURRENCE OF FEBRILE SEIZURES: A CASE REPORT OF A 2-YEAR-OLD BOY WITH COMPLEX FEBRILE SEIZURE - Dimas Tri Anantyo; Ayu Anggraini Kusumaningrum; Nuh Gusta Ady Yolanda; Vinandra - (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: Febrile seizures are seizures associated with fever during childhood that most often occurs in children ages six months-five years, with a peak incidence of 18 months Although febrile seizures generally have a good prognosis, they can signal an underlying serious acute infectious infection. This report aims to present a case of febrile seizures associated with the underlying extracranial infection in Semarang.Method: This report describes the anamnesis, physical examination, and supporting examination in patients with febrile seizures.Case: A 2-year-old boy coming to the ER with complaints of seizures that accompanied by fever, When the child seizures are unconscious, after the seizures the child cries.Discussion: The patient came with seizures accompanied by fever three times before being taken to the hospital, the duration of the seizure ± 10 seconds, with a range of ± 2 hours between the first, and the next seizures, twitching convulsions throughout the body, eyes glared upwards, when the child got the seizure, he was unconscious, and after a seizure, the child cries. Three days before, the child had a fever and a cough with yellowish phlegm. On physical examination, It was found ronchi in both lung fields. From x-ray obtained bronchopneumonia picture. Patients diagnosed with complex febrile seizures and bronchopneumonia.Conclusion: Patients were diagnosed with complex febrile seizures and bronchopneumonia, treated for six days, and sent home because the patient's clinical condition improved. Infection is associated with the incidence of febrile seizures.